2021
DOI: 10.1186/s40644-021-00394-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of diffusion kurtosis tensor MR imaging in characterization of renal cell carcinomas with different pathological types and grades

Abstract: Background To probe the feasibility and reproducibility of diffusion kurtosis tensor imaging (DKTI) in renal cell carcinoma (RCC) and to apply DKTI in distinguishing the subtypes of RCC and the grades of clear cell RCC (CCRCC). Methods Thirty-eight patients with pathologically confirmed RCCs [CCRCC for 30 tumors, papillary RCC (PRCC) for 5 tumors and chromophobic RCC (CRCC) for 3 tumors] were involved in the study. Diffusion kurtosis tensor MR imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It has been shown to offer superior sensitivity over conventional DTI [12]. An appealing aspect of the incorporation of DKI into routine clinical practice is that it can be performed in a straightforward manner, given that the sequence is performed in essentially the same manner as a standard DWI sequence [13], aside from the need for generally higher b values.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to offer superior sensitivity over conventional DTI [12]. An appealing aspect of the incorporation of DKI into routine clinical practice is that it can be performed in a straightforward manner, given that the sequence is performed in essentially the same manner as a standard DWI sequence [13], aside from the need for generally higher b values.…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed DK imaging technique is one RD imaging technique that is based on the principle of measuring the degree of non-Gaussian distribution of water molecule diffusion [23,24]. It has been previously reported that the DK imaging technique has conferred high sensitivity and specificity for detecting tumors in the brain, kidney, liver and prostate, in addition to other diseases, including cerebrovascular infarction, Alzheimer's disease, mild cognitive impairment, Parkinson's disease, multiple sclerosis and aging-related changes in the brain microstructure [8,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 1126 renal lesions from 13 studies, clear cell renal cell carcinomas (RCC) demonstrated higher ADC values than non-clear cell RCCs, low-fat angiomyolipomas, papillary RCCs, and chromophobe RCCs, but lower ADC values than oncocytomas [ 93 ]. Although these results were recently confirmed using either ADC [ 92 ] or kurtosis tensor MR imaging—a more advanced type of DWI analysis [ 94 ]—the moderate sensitivity and specificity reported by these works may be insufficient for DWI to be a reliable single test to differentiate RCC subtypes [ 93 ]. In a study of 46 patients with Von Hippel–Lindau (VHL) disease, ADC at baseline was negatively correlated with the volume doubling time of 100 clear cells RCCs [ 95 ].…”
Section: Diffusion-weighted Renal Imagingmentioning
confidence: 99%